2022
DOI: 10.1038/s41598-022-14558-3
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing antiviral phytochemicals from the leaf extracts of Spondias mombin (Linn) towards the identification of potential SARSCOV-2 inhibitors

Abstract: Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), a pneumonia-like disease with a pattern of acute respiratory symptoms, currently remains a significant public health concern causing tremendous human suffering. Although several approved vaccines exist, vaccine hesitancy, limited vaccine availability, high rate of viral mutation, and the absence of approved drugs account for the persistence of SARS-CoV-2 infections. The investigation of possibly repurposing of phytochemical compounds as therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 131 publications
0
1
0
Order By: Relevance
“…In terms of Geraniin (98% w/w), we have reported in our previousin silico study to possess anti-Ebola and anti-SARS-CoV-2 properties against EBOV secreted Glycoprotein (sGP) and a possible inhibitor interferes with the functioning of SARS-CoV-2 targets (Boadu et al, 2022, Boadu et al, 2021. During the anti-Ebola study, a pharmacophore model generated showed that three aromatic rings, a hydrophobic ring and several hydrogen donors/acceptors were responsible for ant-Ebola activities, although it violated Lipinski's rule of five (Lipinski, Lipinski et al, 1997).…”
Section: Preliminary Phytochemical Screeningmentioning
confidence: 99%
“…In terms of Geraniin (98% w/w), we have reported in our previousin silico study to possess anti-Ebola and anti-SARS-CoV-2 properties against EBOV secreted Glycoprotein (sGP) and a possible inhibitor interferes with the functioning of SARS-CoV-2 targets (Boadu et al, 2022, Boadu et al, 2021. During the anti-Ebola study, a pharmacophore model generated showed that three aromatic rings, a hydrophobic ring and several hydrogen donors/acceptors were responsible for ant-Ebola activities, although it violated Lipinski's rule of five (Lipinski, Lipinski et al, 1997).…”
Section: Preliminary Phytochemical Screeningmentioning
confidence: 99%